Membangun Generasi Cerdas dan Religius melalui Program Bimbingan Belajar dan Islamifest di Gampong - Yus Rijal; Fakhri Yacob; Husnizar; Imran; M. Yusuf (Barkah Publishing, 2025)
This community service activity aims to create an intelligent and religious young generation through the implementation of the Tutoring and Islamifest Program in Gampong Meunasah Krueng, Ingin Jaya District, Aceh Besar Regency. This program is designed to meet the community's needs to improve children's academic abilities and strengthen religious and moral values among adolescents. This service uses a descriptive qualitative approach with participatory methods, which include observation, interviews, and collection of activity documentation. Data were analyzed reflectively by involving students and the community as active participants in the program. The results showed significant progress in the participants' reading and arithmetic skills after participating in regular tutoring. Furthermore, the Islamifest activities, which included various Islamic competitions, thematic studies, and religious arts, successfully increased the spirituality, self-confidence, and social engagement of children and adolescents in the village environment. The community also actively contributed to the success of the program by providing learning facilities and continuing activities after the service through the formation of the